An Inverted U-shaped Relationship? The Impact of Government Subsidies on the R&D Investment of New Energy Companies: Economic Policy Uncertainty and Enterprise Heterogeneity Perspectives - Liu, Manzhi; Wen, Jixin; Liu, Yingjie; Lv, Xueqing; Liu, Qiyao; Lu, Jia; Qin, Ying; Zhang, Linlin (Frontiers in Energy Research, 2022)
Taking 142 new energy listed companies in Shanghai and Shenzhen A-stocks from 2012 to 2018 as the research object, a fixed-effect model was used to study the impact of government subsidies on R&D investment of new energy companies, and analyze the changes in the relationship between the two under the state of economic policy uncertainty and enterprise heterogeneity. The result shows that government subsidies have an inverted U-shaped impact on R&D investment; that is to say that government subsidies will promote enterprise R&D investment within an appropriate range, while excessive subsidies will squeeze out other funds invested by the company for R&D and exacerbate the company’s tendency to invest in fixed assets; compared with fixed-asset investment, economic policy uncertainty has a stronger negative adjustment effect on the relationship between government subsidies and corporate R&D investment. Further research found that in eastern coastal areas of China, the impact of government subsidies on R&D investment is more significant for high-risk preference enterprises and non-state-owned enterprises; while in the central and western regions, the negative adjustment effect of economic policy uncertainty is stronger for low-risk preference enterprises and non-state-owned enterprises. It is recommended that government departments should ensure the stability and continuity of economic policies. The selection of subsidies should be more targeted and more accurate in determining the subsidy funds.